2011
DOI: 10.3109/0142159x.2010.541535
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ perception of professionalism: A qualitative study from Saudi Arabia

Abstract: The students' views should be tallied with other sources of evidences. Nevertheless, they have policy implications on faculty recruitment, development, curriculum reform, and an organizational culture that supports professionalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 28 publications
6
27
1
4
Order By: Relevance
“…The need for such a study was significant in the light of some recent studies at the University of Dammam, Saudi Arabia, a qualitative study conducted by Adkoli. 15 This study revealed that medical students admitted are deficient in information on the acquisition of professional values. According to the study, professionalism was neither taught nor assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for such a study was significant in the light of some recent studies at the University of Dammam, Saudi Arabia, a qualitative study conducted by Adkoli. 15 This study revealed that medical students admitted are deficient in information on the acquisition of professional values. According to the study, professionalism was neither taught nor assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Now it is clearly known that professionalism results in better patient satisfaction and outcomes, is associated with better clinical proficiency in interns, and predicts the incidence of misconduct and malpractice litigation in future clinical practice. 5,15 The frequency of medical errors in the Kingdom of Saudi Arabia was reported to be on the rise. 14 There are a limited number of studies in the literature regarding professionalism among new medical graduates in kingdom of Saudi Arabia and this study is considered one of the first and few quantitative studies that conducted in one of the largest teaching hospital in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Medical students in the Middle East report that the current curriculum is inadequate in nurturing professional behavior. 31 Cross-cultural medical ethics courses introduced at Weill Cornell Medical College in Qatar have demonstrated promise in mediating cultural frictions by promoting trust and tolerance; engaging students in critical thinking; and helping them develop emergent, culturally sensitive professional identities. 33 With the globalization of medical education, efforts should be made to develop curricula that promote the development of contextspecific professional values in non-Western countries.…”
Section: A Proposed Frameworkmentioning
confidence: 99%
“…Pode ser definido como um conjunto de competências relacionadas ao uso criterioso da comunicação, conhecimento, habilidades técnicas, raciocínio clíni-co, emoções, valores, ética e reflexões na prática diária para o benefício do indivíduo e da comunidade 1,2,3 .…”
Section: Introductionunclassified